Teaching writing recount text by using mind mapping - Muhammad Bambang Purwanto (Relawan Jurnal Indonesia, 2022)
The focus of this research was whether teaching writing recount text to tenth grade students at Pemulutan's State Senior High School 1 could be accomplished using mind mapping. This study applied a quasi-experimental design. The use of random assignment is not used in quasi-experimental designs. In the academic year 2021/2022, the population of this study consisted of all tenth grade students of SMA Negeri 1 Pemulutan. The students in tenth grade at SMA Negeri 1 Pemulutan were chosen as the samples, which have been taken using non-random sampling. The experimental group was class (X.2), while the control group was class (X.1). The value of t-obtained was 3.42, and the value of t-table was 2.060 at a significant level of 5%, according the results of t-obtained. Because the t-obtained value was higher than the value in the t-table. The study focuses on finding that teaching writing through mind mapping enabled learners to get higher scores based on the post-test experimental group's and post-test control group's results It was discovered that training tenth grade children to write at SMA Negeri 1 Pemulutan through mind mapping to enhance writing was effective.